Anion exchange HPLC monitoring of mRNA in vitro transcription reactions to support mRNA manufacturing process development - Welbourne, Emma N.; Loveday, Kate A.; Nair, Adithya; Nourafkan, Ehsan; Qu, Jixin; Cook, Ken; Kis, Zoltán; Dickman, Mark J. (Frontiers in Molecular Biosciences, 2024)
mRNA technology has recently demonstrated the ability to significantly change the timeline for developing and delivering a new vaccine from years to months. The potential of mRNA technology for rapid vaccine development has recently been highlighted by the successful development and approval of two mRNA vaccines for COVID-19. Importantly, this RNA-based approach holds promise for treatments beyond vaccines and infectious diseases e.g. treatments for cancer, metabolic disorders, cardiovascular conditions, and autoimmune diseases. There is currently significant demand for the development of improved manufacturing processes for the production of mRNA therapeutics in an effort to increase their yield and quality. The development of suitable analytical methods for the analysis of mRNA therapeutics is critical to underpin manufacturing development and the characterisation of the drug product and drug substance. In this study we have developed a highthroughput, high-performance liquid chromatography (HPLC) workflow for the rapid analysis of mRNA generated using in vitro transcription (IVT).We have optimised anion exchange (AEX) HPLC for the analysis of mRNA directly from IVT. Chromatography was performed in under 6 minutes enabling separation of all of the key components in the IVT, including nucleoside triphosphates (NTPs), Cap analogue, plasmid DNA and mRNA product. Moreover, baseline separation of the NTPs was achieved, which facilitates accurate quantification of each NTP such that their consumption may be determined during IVT reactions. Furthermore, the HPLC method was used to rapidly assess the purification of the mRNA product, including removal of NTPs/Cap analogue and other contaminants after downstream purification, including solid phase extraction (SPE), oligo deoxythymidine (oligo-dT) affinity chromatography and tangential flow filtration (TFF).Using the developed method excellent precision was obtained with calibration curves for an external mRNA standard and NTPs giving correlation coefficients of 0.98 and 1.0 respectively. Intra-and inter-day studies on retention time stability of NTPs, showed a relative standard deviation ≤0.3% and ≤1.5% respectively. The mRNA retention time variability was ≤ 0.13%. This method was then utilised to monitor the progress of an IVT reaction for the production of Covid spike protein (C- Spike) mRNA to measure the increasing yield of mRNA alongside the consumption of NTPs during the reaction.